Report of three cases that received maintenance treatment with risperidone as a mood stabilizer - Fountoulakis, Konstantinos N (BioMed Central, 2004)
INTRODUCTION: The current study is a short report of 3 cases of bipolar patients. MATERIAL AND METHODS: Three bipolar patients were prospectively followed up. All were partial responders to lithium therapy alone, and unresponsive to other therapies (anticonvulsants, antidepressants, typical antipsychotics, various combinations). RESULTS: All manifested complete remission of symptoms after combination therapy with lithium (plasma levels above 0.8 mEq/lt) plus 1–3 mg of risperidone daily. The two of them are still free of symptomatology during the maintenance period for 28 and 38 months respectively. The third patient, after several months during which she was free of symptomatology discontinued lithium against the psychiatrist's advise and received only 3 mg of risperidone daily. For the next 15 months the patient was under risperidone monotherapy and free of symptomatology. She discontinued therapy to become pregnant, the illness recurred several times during pregnancy and after the delivery the patient restarted risperidone therapy. She was free of symptoms for the following 9 months until her last follow-up. DISCUSSION: The current study provides preliminary evidence concerning the long term efficacy of risperidone in the treatment of bipolar patients